2014
DOI: 10.1002/chem.201405295
|View full text |Cite
|
Sign up to set email alerts
|

System with Potential Dual Modes of Metal–Ligand Cooperation: Highly Catalytically Active Pyridine‐Based PNNH–Ru Pincer Complexes

Abstract: Metal-ligand cooperation (MLC) plays an important role in catalysis. Systems reported so far are generally based on a single mode of MLC. We report here a system with potential for MLC by both amine-amide and aromatization-dearomatization ligand transformations, based on a new class of phosphino-pyridyl ruthenium pincer complexes, bearing sec-amine coordination. These pincer complexes are effective catalysts under unprecedented mild conditions for acceptorless dehydrogenative coupling of alcohols to esters at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 72 publications
4
77
0
2
Order By: Relevance
“…In contrast, an example of a singly deprotonated benzylic arm on Re I augments this analogous C−C bond formation with an Re−O bond . Other examples of benzylic pincer deprotonation have shown that Li + associates closely with the π system of the dearomatized ring of the conjugate base . Several cobalt pincer complexes with monoanionic pincer ligands were reported in the last decade (Figure ) .…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, an example of a singly deprotonated benzylic arm on Re I augments this analogous C−C bond formation with an Re−O bond . Other examples of benzylic pincer deprotonation have shown that Li + associates closely with the π system of the dearomatized ring of the conjugate base . Several cobalt pincer complexes with monoanionic pincer ligands were reported in the last decade (Figure ) .…”
Section: Resultsmentioning
confidence: 96%
“…In general, the yield of the corresponding cross‐ester is excellent, whereas in only a few cases were small amounts of homocoupling products of the primary alcohol observed. Recently, Milstein’s group reported the modified Ru PNNH pincer complex 80 , exhibiting secondary amine coordination (Scheme ) 100c. In contrast to the previously described examples 19 and 21 , this new type of Ru pincer complex combines both prevailing MLC modes by amine/amide, as well as aromatization/dearomatization ligand transformation (see section 1.3).…”
Section: Catalysis With Pincer‐type Catalystsmentioning
confidence: 95%
“…Recently our group reported the synthesis and reactivity of a series of analogous [Ru(PNNH)(CO)(H)(Cl)] pincer complexes, which showed exceptional reactivity in hydrogenation and dehydrogenation processes . Exploring the catalytic activity of the PNNH complex 1 , attempted hydrogenation of hexyl hexanoate under 20 bar of H 2 and catalyst loading of 1 mol % in toluene was not successful (Table , entry 1).…”
Section: Methodsmentioning
confidence: 99%